Direct Etherification Reaction of Glycerol Using Alkali Metal Cation (Li+, Na+ and K+) Containing X-Type Zeolites as Heterogeneous Catalysts: Optimization of the Reaction Conditions - Seo Kyung Park (MDPI AG, 2021)
X-type zeolite (XZ-Na) containing Na+ as a cation was synthesized, and XZ-Li and XZ-K were prepared by exchanging the cations of XZ-Na with Li+ and K+, respectively. The specific surface areas, structures, and chemical compositions of the prepared zeolites were analyzed by BET, XRD, and SEM-EDX. The activity of the direct and selective etherifications of glycerol to diglycerol (DG) and triglycerol (TG) were investigated using each zeolite XZ-M (M = Li, Na or K) as a basic heterogeneous catalyst. The etherification reactions of glycerol were carried out at atmospheric pressure while controlling the reaction temperature, reaction time, and the amount of each zeolite. As the amount of each zeolite, reaction time, and reaction temperature increased, the conversion of glycerol also increased, but the selectivities of DG and TG decreased due to the increase in the production of oligomers. When each zeolite was used as a catalyst, the catalytic activity for the conversion of glycerol was observed as XZ-K > XZ-Li > XZ-Na, but the selectivities of DG and TG were observed as XZ-Li > XZ-Na > XZ-K. Especially, 3 wt.% of XZ-Li exhibited the excellent catalytic performance when the etherification of glycerol was optimized and carried out at 280 °C for 2 h: the conversion of glycerol was 89.6% and the yields of DG and TG were 61.2 and 21.2%, respectively.